2013
DOI: 10.1016/j.lindif.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence and working memory control: Evidence from the WISC-IV administration to Italian children

Abstract: Working memory (WM) has been associated with general intelligence (GI). However, evidence is contradictory, as the relationship has in some cases resulted to be very high, and in other cases very low. To explain these differences, it has been argued that WM is an articulated system and only its more attentional components are strictly related with GI. In particular, it has been argued that WM tasks can be located -according to the task characteristics and the subject's age -along a continuum, from the most pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
(27 reference statements)
1
15
0
1
Order By: Relevance
“…This finding indicates that group differences in WM may be attributable to differences in general intelligence. Relationships between WM capacity and intellectual ability have also been documented by studies of typically -19 -developing children and young adults (Ackerman, Beier, & Boyle, 2005;Cornoldi, Orsini, Cianci, Giofrè, & Pezzuti, 2013).…”
Section: Predictive Effect Of Working Memory On Reading and Spelling mentioning
confidence: 81%
“…This finding indicates that group differences in WM may be attributable to differences in general intelligence. Relationships between WM capacity and intellectual ability have also been documented by studies of typically -19 -developing children and young adults (Ackerman, Beier, & Boyle, 2005;Cornoldi, Orsini, Cianci, Giofrè, & Pezzuti, 2013).…”
Section: Predictive Effect Of Working Memory On Reading and Spelling mentioning
confidence: 81%
“…An abundant body of research has shown that processing speed (Coyle, 2013;Jensen, 1998) and WM (Cornoldi, Orsini, Cianci, Giofrè, & Pezzuti, 2013;Demetriou et al, 2013;Giofrè, Mammarella, & Cornoldi, 2013) are involved in intellectual functioning. The present evidence confirms that this relationship may differ, however, in particular groups -as already suggested in the case of children with ADHD, who may struggle with WM tasks despite a high level of intelligence (Cornoldi, Giofrè, Calgaro, & Stupiggia, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the two constructs are closely related, they do not appear to overlap completely and the two constructs can be considered as distinguishable (Conway, Kane, & Engle, 2003). Their relationship is under debate (Martínez et al, 2011) Conway, & Gathercole, 2010), and it has also been argued that highly-controlled WM processes have a greater power for predicting intelligence in typically-developing children (Cornoldi, Orsini, Cianci, Giofrè, & Pezzuti, 2013) than in particular populations (Cornoldi, Giofrè, Calgaro, & Stupiggia, 2013). The idea that different components of WM relate differently to intelligence has found further support: a recent study on 4 th -and 5 th -graders, for instance, supported the relationship between WM and intelligence, but showed that only active WM and visuospatial short-term memory were significantly related to intelligence, while verbal short-term memory did not .…”
Section: Cognitive Processes Involved In Geometry: Working Memory Andmentioning
confidence: 99%